Influence of Number of Parity on Bone Mineral Density among Postmenopausal Women - Alam, Irin Parveen; Haque, Mohd Azharul; Chowdhury, Saleha Begum (Journal of Bangladesh College of Physicians and Surgeons, 2016)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> Introduction- Osteoporosis is a common disease of postmenopausal women and is responsible for considerable morbidity and mortality. The most important single determining factor is low bone mass. Generally accepted risk factors of osteoporosis in women are low body weight, age, low physical activity and cigarette smoking. The effect of parity is controversial. Objective-The main objective of the study was to assess the influence of parity on bone mineral density among the postmenopausal women. Methods-In this study total 75 postmenopausal women aged 51-70 years of with parity 1-13 were studied. Parity was described as the number of births reported by the women. In Journal of Bangladesh College of Physicians and Surgeons Vol. 33, No. 2, April 2015 this study T score of BMD of different bony sites lumber vertebrae and femur were analyzed. BMD were measured in the Institute of Nuclear Medicine at BSMMU. Correlations between BMD values with parity were detected. Results- The mean age of the patients was 60 years with a standard deviation of ±9.32 years. All patients were within 51 to 70 years age range. A significant negative correlation was found in present study between parity and the T score measurement results obtained from L2, L3, L4, L2-4, Femur neck, Trochantor and Wards triangle. This shows mean Tscore of BMD were more negative as number of parity increases. J Bangladesh Coll Phys Surg 2015; 33(2): 75-78 <!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–> Introduction- Osteoporosis is a common disease of postmenopausal women and is responsible for considerable morbidity and mortality. The most important single determining factor is low bone mass. Generally accepted risk factors of osteoporosis in women are low body weight, age, low physical activity and cigarette smoking. The effect of parity is controversial. Objective-The main objective of the study was to assess the influence of parity on bone mineral density among the postmenopausal women. Methods-In this study total 75 postmenopausal women aged 51-70 years of with parity 1-13 were studied. Parity was described as the number of births reported by the women. In Journal of Bangladesh College of Physicians and Surgeons Vol. 33, No. 2, April 2015 this study T score of BMD of different bony sites lumber vertebrae and femur were analyzed. BMD were measured in the Institute of Nuclear Medicine at BSMMU. Correlations between BMD values with parity were detected. Results- The mean age of the patients was 60 years with a standard deviation of ±9.32 years. All patients were within 51 to 70 years age range. A significant negative correlation was found in present study between parity and the T score measurement results obtained from L2, L3, L4, L2-4, Femur neck, Trochantor and Wards triangle. This shows mean Tscore of BMD were more negative as number of parity increases. J Bangladesh Coll Phys Surg 2015; 33(2): 75-78 <!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–>